Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s40123-021-00408-4
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Posterior Capsule Opacification: Incidence, Severity, and Risk Factors

Abstract: Introduction To evaluate the incidence, severity, and risk factors of early-onset posterior capsule opacification (PCO) following uneventful phacoemulsification and intraocular lens (IOL) implantation. Methods Patients with cataracts who underwent phacoemulsification and IOL implantation surgery for 3 months from September 2019 to April 2020 were enrolled. All the subjects completed a comprehensive ocular examination. Retroillumination images of the posterior capsule we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Previous research [4], [10] found that most patients were in the age range of 41 years to 80 years, and Ayuningtyas et al [8] showed a median age of 65 years with a range of 42 years to 87 years. In various studies [11], [12], [13], [14], [15], [16] , the period between patients who underwent cataract surgery and PCO formation has been reported to occur from five months to three years. In this study, PCO diagnosis was established after a median of 12 months, ranging from 8.2 months to 26.3 months after cataract extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research [4], [10] found that most patients were in the age range of 41 years to 80 years, and Ayuningtyas et al [8] showed a median age of 65 years with a range of 42 years to 87 years. In various studies [11], [12], [13], [14], [15], [16] , the period between patients who underwent cataract surgery and PCO formation has been reported to occur from five months to three years. In this study, PCO diagnosis was established after a median of 12 months, ranging from 8.2 months to 26.3 months after cataract extraction.…”
Section: Resultsmentioning
confidence: 99%
“…They insisted that a capsulorhexis size of no more than 5.5 mm is desirable to prevent the development of PCO [ 2 ]. In addition, Gu et al demonstrated incomplete capsulorhexis–IOL overlap as a risk factor for PCO [ 15 ]. Aykan et al also reported a significant reduction in the incidence of PCO with complete capsulorhexis-IOL overlap [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…5,17–20 The earliest measurement of both CDVA and SE was preferred to minimize the late postoperative effects of ocular comorbidities and posterior capsular opacification. 17,21,22…”
Section: Methodsmentioning
confidence: 99%
“…5,[17][18][19][20] The earliest measurement of both CDVA and SE was preferred to minimize the late postoperative effects of ocular comorbidities and posterior capsular opacification. 17,21,22 In terms of complications, the diagnosis of endophthalmitis was defined according to the definition provided in the Endophthalmitis Vitrectomy Study. 23 Persistent corneal edema was defined as the presence of a pseudophakic corneal edema and persistent endothelial cell damage within 30 days of surgery.…”
Section: Outcome Measuresmentioning
confidence: 99%